Native microalgal-bacterial consortia from the Ecuadorian Amazon region: an alternative to domestic wastewater treatment - López-Patiño, Amanda M.; Cárdenas-Orrego, Ana; Torres, Andrés F.; Navarrete, Danny; Champagne, Pascale; Ochoa-Herrera, Valeria (Frontiers in Bioengineering and Biotechnology, 2024)
In low-middle income countries (LMIC), wastewater treatment using native microalgal-bacterial consortia has emerged as a cost-effective and technologically-accessible remediation strategy. This study evaluated the effectiveness of six microalgal-bacterial consortia (MBC) from the Ecuadorian Amazon in removing organic matter and nutrients from non-sterilized domestic wastewater (NSWW) and sterilized domestic wastewater (SWW) samples. Microalgal-bacterial consortia growth, in NSWW was, on average, six times higher than in SWW. Removal rates (RR) for NH4+- N and PO43--P were also higher in NSWW, averaging 8.04±1.07 and 6.27±0.66 mg L-1 d-1, respectively. However, the RR for NO3- -N did not significantly differ between SWW and NSWW and the RR for soluble COD slightly decreased under non-sterilized conditions (NSWW). Our results also show that NSWW and SWW samples were statistically different with respect to their nutrient concentration (NH4+-N and PO43--P), organic matter content (total and soluble COD and BOD5) and physical-chemical parameters (pH, T and EC). The enhanced growth performance of MBC in NSWW can be plausibly attributed to differences in nutrient and organic matter composition between NSWW and SWW. Additionally, a potential synergy between the autochthonous consortia present in NSWW and the native microalgal-bacterial consortia may contribute to this efficiency, contrasting with SWW where no active autochthonous consortia were observed. Finally, we also show that MBC from different localities exhibit clear differences in their ability to remove organic matter and nutrients from NSWW and SWW. Future research should focus on elucidating the taxonomic and functional profiles of microbial communities within the consortia, paving the way for a more comprehensive understanding of their potential applications in sustainable wastewater management.